Intentions for bilateral mastectomy among newly diagnosed breast cancer patients. Issue 7 (27th December 2012) - King, Lesley; O'Neill, Suzanne C.; Spellman, Elizabeth; Peshkin, Beth N.; Valdimarsdottir, Heiddis; Willey, Shawna; Leventhal, Kara Grace; DeMarco, Tiffani; Nusbaum, Rachel; Feldman, Elizabeth; Jandorf, Lina; Schwartz, Marc D.
Abstract Background Recent trends suggest that bilateral mastectomy (BM) is on the rise among women diagnosed with unilateral breast cancer. Few studies have investigated the factors associated with the decision to have more aggressive surgery among young, high risk patients. Methods As part of a larger study, 284 women aged 50 and under completed an initial survey within 6 weeks of a breast cancer diagnosis. We assessed sociodemographics, medical and family history variables, treatment recommendations, preferences and concerns, distress, perceived risk, knowledge, and neuroticism. We used multiple regression with backward entry to assess the relationship between these variables and our outcomes of decisional conflict and intentions for BM. Results Higher decisional conflict was associated with being less educated, unmarried, more anxious and less likely to have received a surgical recommendation. Preference for BM was associated with higher neuroticism, perceived risk for contralateral breast cancer, pre‐testing risk of carrying a BRCA1/2 mutation, having received either a surgical recommendation (vs. no recommendation), and lower preference for lumpectomy. Conclusions For younger women, a surgical recommendation is associated with lower decisional conflict and stronger intention for BM. Results highlight the importance of effective risk communication and decision support between a woman and her surgeon. J. Surg. Oncol. 2013;107:772–776. © 2012 Wiley Periodicals, Inc.